Autoethnography of a Queer Racialized Athlete - Nickholas Basilio; William Bridel (Spectrum, 2025)
Over four decades of research has suggested that there is a high prevalence of homophobia and transphobic attitudes, behaviors, policies, and practices within sport and physical activity. These realities serve as barriers or deterrents to participation for many 2SLGBTQIA+ people and groups and can also make sport and physical activity unwelcoming and even unsafe for those who choose to participate. In this important body of work, there remains a glaring absence of racialized 2SLGBTQIA+ athletes’ experiences. To help to address this gap, the primary purpose of my research was to explore how marginalized communities experience overlapping forms of discrimination in sport. Adopting an autoethnographic methodological approach, I wrote a series of vignettes about my own experiences as a queer racialized athlete in Western Canada. While writing the vignettes was a reflective process in and of itself, I also followed the tenets of critical discourse analysis to think about my experiences in relation to the broader cultural context. This resulted in the creation of three themes: intersectionality, microaggressions, and homophobia. Each worked independently and together to create an unsafe space for me, impacting my athletic experiences and life more broadly in negative ways. Reflecting on my experiences critically, however, also allowed me to think about resistance and resiliency. My hope is that my work contributes to existing literature and provide insight for other queer racialized athletes who may have had similar experiences in sport.